Natural variation in HvAT10 underlies grain cell wall-esterified phenolic acid content in cultivated barley - Houston, Kelly; Learmonth, Amy; Hassan, Ali Saleh; Lahnstein, Jelle; Looseley, Mark; Little, Alan; Waugh, Robbie; Burton, Rachel A.; Halpin, Claire (Frontiers in Plant Science, 2023)
The phenolic acids, ferulic acid and p-coumaric acid, are components of plant cell walls in grasses, including many of our major food crops. They have important health-promoting properties in grain, and influence the digestibility of biomass for industrial processing and livestock feed. Both phenolic acids are assumed to be critical to cell wall integrity and ferulic acid, at least, is important for cross-linking cell wall components, but the role of p-coumaric acid is unclear. Here we identify alleles of a BAHD p-coumaroyl arabinoxylan transferase, HvAT10, as responsible for the natural variation in cell wall-esterified phenolic acids in whole grain within a cultivated two-row spring barley panel. We show that HvAT10 is rendered non-functional by a premature stop codon mutation in half of the genotypes in our mapping panel. This results in a dramatic reduction in grain cell wall-esterifed p-coumaric acid, a moderate rise in ferulic acid, and a clear increase in the ferulic acid to p-coumaric acid ratio. The mutation is virtually absent in wild and landrace germplasm suggesting an important function for grain arabinoxylan p-coumaroylation pre-domestication that is dispensable in modern agriculture. Intriguingly, we detected detrimental impacts of the mutated locus on grain quality traits where it was associated with smaller grain and poorer malting properties. HvAT10 could be a focus for improving grain quality for malting or phenolic acid content in wholegrain foods.